Caracterização funcional da proteína XAC1201 envolvida na patogenicidade de Xanthomonas citri subsp. citri - Vieira, Flávia Campos Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The ORF XAC1201 of Xanthomonas citri subsp. citri (Xac) encodes a hypothetical protein and when knocked out by transposon insertion leds to changes in the pathogenicity of the bacterium in citrus. The ORF XAC1201 has 819 bp and encodes a protein with a molecular mass of 29.1 kDa. The coding region was cloned into the expression vector pET SUMO and His-SUMO-XAC1201 fusion protein was expressed in Escherichia coli BL21 (DE3) pLysS strain. The best condition for protein expression in soluble form was 28°C and 250 rpm for 4 hours in the presence of 0.2 mM IPTG. Purification was performed by immobilized metal ions affinity chromatography (IMAC) on a Ni2+-Sepharose column and the non-fusion protein was obtained after digestion with SUMO protease and new chromatography on Ni2+-Sepharose column. The final process yield was 3.18% of the total protein, and the protein was obtained highly pure and in the native form. The identity of the purified protein was confirmed by mass spectrometry analysis with sequence coverage above 80%. Enzymatic assays were made to verify phosphohydrolases and histidine kinase activities, however, the results are inconclusive. It is suggested that XAC1201 is a ubiquitous protein and plays an ancestral role, since it is found in several Phyla within the Bacteria Domain. Obtaining this protein in pure, soluble and native form is the first step towards characterization studies of its function. Since this protein is present not only in Xac but has a ubiquitous presence in many other bacterial groups, the understanding of its function is of great interest to many areas

A ORF XAC1201 de Xanthomonas citri subsp. citri (Xac) codifica uma proteína hipotética que, quando nocauteada por inserção de transposon, leva a alterações na patogenicidade da bactéria em citros. A ORF possui 819 pb e codifica a proteína XAC1201 que possui uma massa molecular de 29,1 kDa. A região codificadora foi clonada no vetor de expressão pET SUMO e a proteína de fusão His-SUMO-XAC1201 foi expressa na Escherichia coli linhagem BL21(DE3) pLysS. A melhor condição para expressão da proteína na forma solúvel foi a 28ºC e 250 rpm por 4h na presença de 0,2 mM IPTG. A purificação foi realizada por cromatografia de afinidade com íons metálicos imobilizados (IMAC) em coluna de Ni2+-Sepharose e a proteína de não fusão foi obtida após digestão com SUMO protease e nova cromatografia em coluna de Ni2+-Sepharose. O rendimento final do processo foi de 3,18% da proteína total, tendo a proteína recombinante nativa sido isolada com alto grau de pureza e na forma nativa. A identidade de XAC1201 recombinante foi confirmada pelas análises de espectrometria de massas, com mais de 80% de cobertura da sequência. Foram realizados testes enzimáticos para verificar as prováveis atividades de fosfohidrolase e histidina quinase, porém, estes testes não foram conclusivos. A análise de frequência e diversidade da ORF XAC1201 em bancos de dados sugere que se trata de uma proteína ubíqua e com função ancestral, presente em diversos filos dentro do Domínio Bacteria. A obtenção desta proteína na forma pura, solúvel e nativa é o primeiro passo para os estudos de caracterização da sua função e, devido à presença de alta identidade desta sequência com muitos outros grupos bacterianos, a elucidação da função desta proteína será de grande interesse, não apenas para Xac, como também para outros microrganismos
Keywords: Cancro citrico; Proteínas; Xanthomonas; Genetica vegetal; Bacterias fitopatogenicas; Expressão gênica; Gene expression